2022
DOI: 10.1021/acsbiomaterials.1c01369
|View full text |Cite
|
Sign up to set email alerts
|

Design of a Ratiometric Plasmonic Biosensor for Herceptin Detection in HER2-Positive Breast Cancer

Abstract: Breast cancer is the most common cause of cancer death in women; therefore, its early detection and treatment are crucial. To achieve this goal, we designed an optical sensor based on direct interaction of trastuzumab [Herceptin (HER)], a monoclonal antibody used to treat HER2-positive breast cancer, with plasmonic nanoparticles. Surface-modified gold nanoparticles (AuNPs) have gained considerable attention in biosensing techniques over the last years, which actuated these nanoparticles to the heart of various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…Nanobiosensors have remarkable potential for the detection of various microbes, disease biomarkers, environmental pollutants, and drug delivery (e.g., pathogen in food, blood pathogen biomarkers in blood) [ 47 , 48 ]. They also have the potential to detect early cancer in body fluids (e.g., breast cancer) [ 49 ]. Based on research progress in this area, nanobiosensor devices could move from the laboratory to the commercial level.…”
Section: Nanobiosensormentioning
confidence: 99%
“…Nanobiosensors have remarkable potential for the detection of various microbes, disease biomarkers, environmental pollutants, and drug delivery (e.g., pathogen in food, blood pathogen biomarkers in blood) [ 47 , 48 ]. They also have the potential to detect early cancer in body fluids (e.g., breast cancer) [ 49 ]. Based on research progress in this area, nanobiosensor devices could move from the laboratory to the commercial level.…”
Section: Nanobiosensormentioning
confidence: 99%
“…RSM was used to optimize the effects of ethanol concentration, solvent volume ratio, and extraction duration on the extraction process of Duliang formula. [13][14][15][16][17][18][19][20][21] The data were analyzed with Design-Expert (8.0.6) statistical software, and the multiple linear regression fitting equations were obtained: Y = 0.5117 + 0.1198X1 + 0.0415X2 + 0.0492X3 − 0.0122X1X2 + 0.0423X1X3 + 0.0176X2X3.…”
Section: Optimization and Prediction Of Process Parametersmentioning
confidence: 99%
“…RSM was used to optimize the effects of ethanol concentration, solvent volume ratio, and extraction duration on the extraction process of Duliang formula. 1321 The data were analyzed with Design-Expert (8.0.6) statistical software, and the multiple linear regression fitting equations were obtained:The quadratic polynomial regression equation was:The results show that the established multivariate linear model ( P > .05) fitted poorly, and was not significant, so it cannot pass the test. The quadratic polynomial model was significant ( P < .05), which showed that the experimental results can be highly correlated with the prediction model.…”
Section: Data Process and Response Surface Optimizationmentioning
confidence: 99%
“…Optimization of Prescription by Central Composite Design Method. The amount of organic solvent(acetone) and the ratio of drug amount to excipient amount were selected as two conditions for prescription optimization using the central composite design response surface method (CCD design method) [19][20][21] using Design Expert 12 software [22].…”
Section: Single-factor Testmentioning
confidence: 99%